Everyday challenges for mothers with Spinal Cord Injury: a qualitative study - Gunnbjørg Aune (Scandinavian Journal of Disability Research, 2012)
The aim of this study was to explore how women with traumatic spinal cord injury (SCI) manage their daily lives after becoming mothers and if they experienced barriers in society. Five women were interviewed, aged 25–40 years, who had incurred a traumatic SCI two to twenty years previous to their first child being born. All the participants expressed a wish to carry out infant care tasks and to take part in their children's activities. The participants used welfare arrangements to manage certain tasks. They faced challenges in the form of physical barriers in their surroundings, as well as various degrees of struggle related to social services. Statements from five Norwegian women with SCI point to unique practical and emotional experiences of becoming mothers. Their reports also elucidate the lack of knowledge among professionals related to motherhood and SCI.